Glasshouse locating based on SWARA-COPRAS approach - Haghnazar Kouchaksaraei, Ramtin; Hashemkhani Zolfani, Sarfaraz; Golabchi, Mahmood (International Journal of Strategic Property Management, 2015)
Glasshouse is a kind of greenhouse that is larger than prevalent greenhouses. Glasshouses may have wide various applications and totally, is more applicable than greenhouse. One important point about glasshouse that should be considered is selecting a good location. Besides, finding a suitable location for this purpose is so hard because establishing a glasshouse needs a large area. Financial justification which is a major issue in glasshouse Investments highlights the importance of its locating. This research is based on strategic property management perspectives and its results can be used to properly locate an economically justifiable glasshouse in both governmental and private levels. There are some other important criteria affects on this issue. This research aimed at presenting new hybrid framework for glasshouse locating based on two MCDM methods. SWARA and COPRAS are applied in this research for glasshouse locating. This methodology for the first time is applied in a research. SWARA is applied for evaluating criteria and COPRAS is applied for evaluating alternatives. For illustrating the research methodology, a case study in Tehran, Iran is presented in the research. This research can be useful as a framework for this aim and also has the advantage to apply in other research areas. First Publish Online: 19 Jun 2015